The Use of Minangkabau Proverbs of Contrast Meanings by Minangkabau Society in Medan - Meisuri Meisuri; Syamsul Bahri (BIRCU, 2019)
The purpose of this study is to find out a complete picture of local wisdom on the use of Minangkabau proverbs that have contrast meanings by the Minangkabau society in Medan North Sumatera, Indonesia. The research used descriptive qualitative method, by conducting interview as well as questionnaires distribution on provided proverbs to a total of 60 respondents from different regions of Minangkabau community, namely Kota Matsum I, II, III and IV. The data were collected and classified based on the various fields of Social Culture, Economy, Politics, Law, and Religion which were then analyzed by interpreting the meaning of contrast contained in the proverbs relating to the customs and traditions they practiced in daily life. It was found that despite the strong evidence on philosophy of cultural values and openness toward the modernization, this people have been consistently using the contrasted-meaning proverbs in their almost all-different-contexts of conversation. It also showed that the use of Minangkabau language as local language, has contributed to the field of language and literature studies, especially in the area of ethnical proverb that could enrich the repertoire of Indonesian, as the national language.